2016
DOI: 10.1111/imig.12271
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese Scientists’ Migration: a study on the 2008 crisis aftermath

Abstract: In the economic and social aftermath of the 2008 crisis there has been an important and growing new wave of highly qualified Portuguese emigration comprising scientists. No or very few public policies have been designed to reverse this phenomenon, risking the consequences of brain drain. International literature argues that professional reasons are central to scientists’ decision to migrate, even after the 2008 crisis. Spending some time in a foreign country to study, research, or teach, is perceived as a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
2
13
0
3
Order By: Relevance
“…Later on in his interview, Jaime clearly cites “academic inbreeding” as being a significant barrier to finding an initial position at a Spanish university, because “it is well known that Spanish university lecturers are, overwhelmingly, former PhD students from the same university.” Jaime has no doubt: “Merit and talent are more valued in Mexico than in Spain.” Inbreeding, the lack of job opportunities and excessive rigidity are characteristics identified by most of the interviewees when describing Italian and Spanish academia. This is line with the existing literature on academic mobility, which has demonstrated that low wages, difficult working conditions, meagre research funding, and a lack of fair competition are the rule rather than the exception in the academic sector in Southern Europe (King & Conti, ; Galán & Agasisti, ; Ganga et al, ). By contrast, the literature has shown that Mexican academia is relatively open to new, foreign arrivals (Castaños Rodríguez, ; Izquierdo, ).…”
Section: Methodssupporting
confidence: 90%
See 3 more Smart Citations
“…Later on in his interview, Jaime clearly cites “academic inbreeding” as being a significant barrier to finding an initial position at a Spanish university, because “it is well known that Spanish university lecturers are, overwhelmingly, former PhD students from the same university.” Jaime has no doubt: “Merit and talent are more valued in Mexico than in Spain.” Inbreeding, the lack of job opportunities and excessive rigidity are characteristics identified by most of the interviewees when describing Italian and Spanish academia. This is line with the existing literature on academic mobility, which has demonstrated that low wages, difficult working conditions, meagre research funding, and a lack of fair competition are the rule rather than the exception in the academic sector in Southern Europe (King & Conti, ; Galán & Agasisti, ; Ganga et al, ). By contrast, the literature has shown that Mexican academia is relatively open to new, foreign arrivals (Castaños Rodríguez, ; Izquierdo, ).…”
Section: Methodssupporting
confidence: 90%
“…rigidity are characteristics identified by most of the interviewees when describing Italian and Spanish academia. This is line with the existing literature on academic mobility, which has demonstrated that low wages, difficult working conditions, meagre research funding, and a lack of fair competition are the rule rather than the exception in the academic sector in Southern Europe (King & Conti, 2013;Galán & Agasisti, 2014;Ganga et al, 2016). By contrast, the literature has shown that Mexican academia is relatively open to new, foreign arrivals (Castaños Rodríguez, 2011;Izquierdo, 2015).…”
Section: Arrival In Mexico: Diversity and Complexity Of Academic Casupporting
confidence: 84%
See 2 more Smart Citations
“…from 2006 to 2012. These changes could be associated to the consequences of the recent economic and financial crisis, such as immigration and emigration trends (Cairns, 2011;Ganga et al, 2016;Fonseca and McGarrigle, 2014) and recent plans for territorial spatial planning and protection of forest against forest fires (Mateus and Fernandes, 2014;. Urban sprawl's complexity and magnitude motivated the European Commission to recommend actions to ameliorate their impacts and coordinate land use policies, within the European Cohesion Policy 2007-2013 period (CEC, 2006;EEA, 2006).…”
mentioning
confidence: 99%